Optimization of the flow conditions in the spawning ground of the Chinese sturgeon (Acipenser sinensis) through Gezhouba Dam generating units - Anyang Huang (Nature Portfolio, 2021)
Abstract Chinese sturgeon (Acipenser sinensis) is a critically endangered species, and waters downstream from Gezhouba Dam are the only known spawning ground. To optimize the velocity conditions in the spawning ground by controlling the opening mode of Gezhouba Dam generator units, a mathematical model of Chinese sturgeon spawning ground was established in FLOW-3D. The model was evaluated with velocity measurements, and the results were determined to be in good agreement. By inverting the 2016–2019 field monitoring results, the model shows that the preferred velocity range for Chinese sturgeon spawning is 0.6–1.5 m/s. Velocity fields of different opening modes of the generator units were simulated with identical discharge. The suitable-velocity area was maximal when all units of Dajiang Plant of Gezhouba Dam were open. For discharges below 12,000 m3/s, most of the area was suitable; for discharges above 12,000 m3/s, the suitable area rapidly decreased with increasing discharge. A comparison of suitable areas under high-flow showed that at discharges of 12,000–15,000 m3/s, opening 11–13 units on the left side was optimal. For discharges above 15,000 m3/s, all units should be open. We used these results to recommend a new operation scheme to support the conservation of Chinese sturgeon.